On the origins of national identity - Felix Kersting; Nikolaus Wolf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
What are the origins of national identity? We extend the model by Alesina et al. (2019) to analyze the incentives of elites to use specific types of identity policies in response to shocks, and the extent to which such policies should be effective. To elicit changes in identity we use data on first names given in German cities between 1800 and 1875. We show that parents in cities treated by nation building policies responded by choosing first names of German origin for their children. To control for familyspecific confounding factors, we exploit within family variation. We also show that the response can be conditional on cultural distance to the elite. Finally, Germanic first names had remarkable predictive power for behaviour. We find that individuals with Germanic first names made different marriage choices and were more likely to get actively involved and decorated during the German-French War in 1870/71 and the First World War.
Keywords: 330